If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + (3 + 4) + -3y = x Combine like terms: 3 + 4 = 7 2x + (7) + -3y = x 2x + 7 + -3y = x Reorder the terms: 7 + 2x + -3y = x Solving 7 + 2x + -3y = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 7 + 2x + -1x + -3y = x + -1x Combine like terms: 2x + -1x = 1x 7 + 1x + -3y = x + -1x Combine like terms: x + -1x = 0 7 + 1x + -3y = 0 Add '-7' to each side of the equation. 7 + 1x + -7 + -3y = 0 + -7 Reorder the terms: 7 + -7 + 1x + -3y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 1x + -3y = 0 + -7 1x + -3y = 0 + -7 Combine like terms: 0 + -7 = -7 1x + -3y = -7 Add '3y' to each side of the equation. 1x + -3y + 3y = -7 + 3y Combine like terms: -3y + 3y = 0 1x + 0 = -7 + 3y 1x = -7 + 3y Divide each side by '1'. x = -7 + 3y Simplifying x = -7 + 3y
| 6+8=214 | | 2a-12=7a+8 | | 5x+30=3x-6 | | 3w-1=2w-6 | | 4x+2=-2x+8 | | -62+x-10x=100 | | 1/2-9=-5 | | -106+6x+x=97 | | 4e^2x=84 | | 6e-4f-10e-f= | | 3y+(8y+8)=360 | | 2x-(3-2x)=x+6 | | x^2+28x+48=0 | | 26x=8 | | (X+4)(x^2-3x+2)= | | 6=h-2/7 | | 3y+(4y+4)=180 | | 5*(x-2)=3*(x+4)+6 | | -3x-5y=-3 | | 6=x/30 | | x=20-10P | | 6x+28=14x-24 | | 2.5(x-3)+17x=10.8(x+15) | | 9/2=x/24 | | 200=y/.035 | | 6(5+m)=5(1+m) | | 7(y+2)+5= | | 91u-28=-494 | | (-25)=(-6)a-43 | | 0.50c+(0.40)(600-c)=280 | | x*3+142=x*13-8 | | 2cosx=-3insx |